Respostas

A melhor resposta!
2014-05-09T21:44:48-03:00
 \sqrt{ \frac{x}{y}  \sqrt[3]{ \frac{y}{x} } } = \sqrt{\sqrt[3]{  \frac{ x^{3} }{ y^{3} } .\frac{y}{x} } } = \sqrt[6]{  \frac{ x^{2} }{ y^{2} } }= \sqrt[3]{  \frac{x}{y} }=  \frac{ \sqrt[3]{x} }{ \sqrt[3]{y} }

O inverso será:

\frac{ \sqrt[3]{y} }{ \sqrt[3]{x} } \frac{ \sqrt[3]{y} }{ \sqrt[3]{x} } =\frac{ \sqrt[3]{y} .\sqrt[3]{ x^{2} }}{ \sqrt[3]{x}.\sqrt[3]{ x^{2} } } =\frac{ \sqrt[3]{ x^{2}y }}{ x} }

Letra b)
4 3 4
Obrigado pela escolha!
Não tem de quê rs